Mengungkap Rahasia Kecakapan Bahasa yang Unggul dari Guru Bahasa Inggris: Sebuah Studi Wawancara - Atmojo, Arief Eko Priyo (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
This study tries to shed light on what makes the English teacher’s proficiency excellent and how these factors help the English teacher achieve excellent proficiency. One female English teacher from a private secondary school participated in this study. Her excellent English proficiency is proven by some proficiency test certificates such as TOEFL and CEFR. Data were garnered through a series of semi-structured interviews based on well-prepared interview guidelines. The principles of data saturation were applied to ensure the credibility of the data. The data analysis was done by employing thematic content analysis. The results suggest that there are four main factors which contribute to the English teacher’s excellent proficiency. These factors include high self-motivation, long learning experience, diverse kinds of exposure, and various kinds of practices. Several affective factors like the feeling of fun, enjoyment, and interest also contribute to the process of language learning and acquisition which lead to excellent English proficiency. Further studies on English proficiency are still encouraged with different methods, settings, and contexts.